Modern Jus Post Bellum – Finding a New Branch of International Justice and Law - Lech, Marcin (Polish Review of International and European Law, 2020)
The arguments put forward in this article concern ideas about jus post bellum as an urgently needed and hopefully emerging branch of a new international legal order based on fully reasoned ethical principles. The presented views refer to justifying this new international legal order with respect to the necessary parallel transformation of the utility of armed response and, particularly, lethal force to meet modern-day and future conflicts. While it is possible to find at least partial answers, many more questions for future development will emerge in order to truly establish what promotes and fulfils the actual achievement of a stable, safe, lasting, and just peace. Therefore, the object of this research into the legal and ethical possibilities is primarily to assess the quality of a new conceptualisation of international justice and law. This allows for the formation of new law jus post bellum and the nature of peace, which might induce the necessary sociopolitical transformation to sustain a just peace. The exclusive reference to moral obligations in the theorisation of the transition from conflict to peace too often fails to recognise the existing framework of the legal rules and principles involved. While analysed from the perspective of International humanitarian Law and the perspective of the independence of nation-states, it characterises asymmetric warfare and the question about the causes driving states’ and other communities’ actions, particularly casus belli. The new interdisciplinary rethinking exposed below can only result in a complex conclusion because jus post bellum in the age of global transitional justice could prepare new judicial frameworks, as well as true and real justice after the end of war.